Morphophysiological characteristics of (Coffea arabica L.) in different arrangements: Lessons from a 3D virtual plant approach - Rakocevic, Miroslava; Androcioli Filho, Armando (Coffee Science - ISSN 1984-3909, 2011)
3D vegetative structural and functional models are useful in simulations of ecophysiological and biophysical processes. The main objective of this study was to model a 3D Coffea arabica L. structure. The specific aim was to use 3D mock-ups for analysis of vertical leaf and berry distribution and light interception in coffee crops cultivated in different planting densities and arrangements. The mock-ups were built after abstraction and codification by VPlants, based on morphological measurements (orthotropic shoot height and its number of internodes; positions of second to fourth branching order plagiotropics; internode number on first to fourth branching order plagiotropics number of leaf pairs), and several hypotheses. Mock-ups were visualized in PlantGLViewer, while Silhouette to Total Area Ratio (STAR), leaf area (LA) and berry distribution were processed in VegeSTAR. Planting arrangements influenced STAR when the plants were grown in a low density (6,000 plants ha-1). Plant density had a significant effect on the number of berries in square arrangements. The higher layers were occupied by first order foliage and few berries, allowing more light to pass to the lower canopy layers. Berries were abundant in the first and second order plagiotropic branches, in the highest and middle layers. Light distribution was more uniform than leaf area distribution, indicative of a disperse foliage and efficient space occupation. STAR correlated strongly with berry number, especially in the upper, less shaded canopy layers, where flower induction was the most intense.